2012
DOI: 10.1134/s1023193512070130
|View full text |Cite
|
Sign up to set email alerts
|

Study of pH correction process of chloride-bicarbonate dilute solutions by electrodialysis with bipolar membranes

Abstract: The pH of a dilute chloride-hydrocarbonate solution and the concentrations of chloride ions and carbonic acid anions at the outlet of the alkaline and acid chambers of the electrodialysis cell formed by bipo lar and anion exchange membranes were determined. The decrease in the concentration of hydrocarbonate ions in the alkaline chamber with growth of current density was not equal to its increase in the acid chamber. This disbalance was caused by two concurrent processes: the electromigration ion transport thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…We write the flow balance equations for all components (j = 1, … 9) in the acid and alkaline compartments. , ( 5,8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We write the flow balance equations for all components (j = 1, … 9) in the acid and alkaline compartments. , ( 5,8).…”
Section: Methodsmentioning
confidence: 99%
“…In electro-membrane processes for adjusting pH of dilute solutions, electrodialyzers with a two-compartment unit cell consisting of monopolar and bipolar membranes are used. The process of pH correction of model binary electrolytes and multi-ion chloride-sulfate-bicarbonate solutions in an electrodialysis cell with bipolar and anion-exchange membranes was theoretically and experimentally studied [5]. The authors showed that from a practical point of view, an electrodialyzer circuit with bipolar and anion-exchange membranes can be effectively used to alkalize technological solutions, while a cation-exchange membrane scheme is preferred for acidification of solutions.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 There is also little precedent for modeling the transport of dilute carbon species in seawater feedstocks used for DOC. 7,41 Models that relate the chemistry and material properties of BPMs to the energy intensity of BPM-ED are therefore warranted. 42 In this work, we demonstrate a comprehensive model of BPM-ED based on our prior work modeling multi-component transport in BPMs, 27 now with the homogeneous reaction kinetics of reactive carbon species (eqn (2)-( 5)).…”
Section: Paper Energy and Environmental Sciencementioning
confidence: 99%
“…39,40 There is also little precedent for modeling the transport of dilute carbon species in seawater feedstocks used for DOC. 7,41 Models that relate the chemistry and material properties of BPMs to the energy intensity of BPM-ED are therefore warranted. 42 In this work, we demonstrate a comprehensive model of BPM-ED based on our prior work modeling multi-component transport in BPMs, 27 now with the homogeneous reaction kinetics of reactive carbon species (Eq.…”
Section: Introductionmentioning
confidence: 99%